Ethnobotany - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Ethnobotany: principles and application by C M Cotton 1996 424pp ISBN 0 471 95537 X Pbk UKL24.95